Preparing teachers to work with multilingual learners - Wernicke, Meike 1968-; Hammer, Svenja; Hansen, Antje 1967-; Schroedler, Tobias 1984- (Bilingual education & bilingualism, 2021)
This book examines a diverse range of approaches to multilingualism in teacher education programmes across Europe and North America. It studies how pre-service teachers are being prepared to work in multilingual contexts and the key features of current initiatives that address the linguistic and cultural diversity of their respective countries